Foodborne Pathogenic Bacteria Detection: An Evaluation of Current and Developing Methods - Zhang, Grace (The Meducator, 2013)
Epidemics arising from foodborne pathogenic bacteria are a major public health concern. There is a critical need for the development and integration of sensitive and effecient methods for foodborne pathogen detection. Beyond this, detection should ideally be rapid, inexpensive, and easy to operate without extensive training or expertise. Although conventional techniques, involving plating followed by various biochemical tests can reliably detect bacteria at low concentrations, the time required to obtain a result is often impractical. Techniques used in conjunction with conventional methods include immunological tests and nucleic acid-based tests; these have been adapted for simultaneous screening of multiple bacterial strains. Flow cytometry has recently been applied to bacterial detection with considerable success. Biosensors, devices that convert biological activity into a measurable electrical signal, have recently gained attention as a potential method for rapid sample screening. This review aims to summarize and evaluate current methods for foodborne pathogenic bacteria detection.